Uncertainty Control Method for Non-Uniform Wear of the Driving Mechanism of Flapping Wing Aircraft - Yujia Jin; Xingyu Chen; Keke Wang; Deyin Jiang; Jingyi Liu; Huan Pang (Drones)
Flapping wing aircrafts have demonstrated unique advantages in military and civil fields due to their bio-inspired flight mechanisms. However, non-uniform wear in driving mechanisms remains a critical reliability concern during prolonged operation. This study presents a stochastic wear prediction framework that systematically integrates joint clearance dynamics, contact force variations, and material interaction parameters. Through accelerated life testing with flight condition simulations, the method establishes quantitative correlations between multi-source variables and wear progression patterns. Experimental validation confirms the framework’s effectiveness in predicting asymmetric wear distribution, with comparative analysis showing significant improvements in prediction accuracy over conventional single-factor models. The results identify three dominant wear contributors: dynamic clearance fluctuations, impact force randomness, and material compatibility limitations. These findings directly support the development of adaptive lubrication systems and wear-resistant material selection guidelines, offering practical solutions for enhancing flapping wing aircrafts’ reliability in complex operational scenarios.